Statistical analysis for the prediction of in-situ characteristic strengths of concrete using various non-destructive tests - Tang, Man Hoi. (2009)
Various correlation curves for the non-destructive test methods with cores and standard specimens were obtained. The test methods used were rebound hammer, ultrasonic pulse velocity, Windsor probe, Lok-test and pulloff. Multilevel correlations were found to improve the fit of the in-place tests data.